Description of five new species of Zodariidae Thorell, 1881 (Araneae) from Yunnan, China - Zhang, Haibin; Li, Qingliang; Yang, Zizhong; Zhang, Feng (Zootaxa, 2025)
Five new ant-eating spiders from Yunnan, China, are described: Asceua banlaoensis sp. nov. (♂), A. nangunhe sp. nov. (♂♀), Euryeidon cervicornis sp. nov. (♂♀), Mallinella acutidentata sp. nov. (♂♀) and M. tongbiguan sp. nov. (♂♀); the habitus and copulatory organs are documented, and a distribution map is provided for all new species. The association between males and females of Euryeidon cervicornis sp. nov. was confirmed by genetic similarity (COI barcoding).